Institutional Effectiveness for Drought Early Warning, Early Action and Early Finance in Kenya - Acuda Opeto, Aaron; Osei-Amponsah, Charity; Amarnath, Giriraj (CGIAR System Organization, 2022)
This case study focuses on drought conditions to analyse the early warning, early action and early finance initiatives required to reduce disaster impacts in Kenya. It particularly follows the ongoing multi-season Horn of Africa drought (2014-2022) where Kenya is located. The case study further investigates the effectiveness of governance and institutional arrangements in place, such that socially inclusive systems and processes for responding to climate change can be developed and implemented.